Clinical and imaging characteristics of hematologic disease complicated by air leak syndrome: A STROBE-compliment observational study. Issue 20 (15th May 2020) - Zhang, Kemin; Shi, Bing; Zhai, Qiang; Jiang, Lihui; Wang, Xiaoxue; Jiang, Shan; Sun, Hongyan
Abstract : Abstract: There are limited systematic studies on hematologic disease complicated by air leak syndrome (ALS). Physicians in radiology departments and hematology departments have a limited awareness of ALS. The aim of this study was to explore the similarities and differences in clinical data between the clinical group and imaging group in patients with hematologic disease complicated by ALS. Clinical and CT data for 59 patients with hematologic disease complicated by ALS in our hospital were retrospectively reviewed. Patients were assessed by clinical grouping and image grouping. Data were compared between groups, and P  < .05 was considered statistically significant. Dyspnea occurred more often in the allo-HSCT (allogeneic hematopoietic stem cell transplantation) group than that in the non–allo-HSCT group (68.8% vs 4.7%, P  < .001), there were statistically significant differences in inducing factors between groups, and differences in other aspects were not statistically significant. Chest tightness and dyspnea occurred more often in the allo-HSCT with BO/BOOP (bronchiolitis Obliteran/bronchiolitis obliterans organizing pneumonia) group than those in the allo-HSCT without BO/BOOP group (80.0% vs 9.1%, P  = .013), and differences in other aspects were not statistically significant. Chest pain occurred more often in the HPT (hydropneumothorax) group than that in the other 3 groups (pure pneumothorax [PT], pulmonary interstitial emphysema [PIE], complex ALS) (71.4% vs 11.1%, 0.0%, and 26.5%, P  = .005); ALS thickness in the HPT group was greater than that in the other 2 groups (PIE and complex ALS) (19.7 vs 3.5 cm and 9.5 cm, P  = .001); catheter drainage occurred more often in the HPT group than that in the other three groups (PT, PIE, complexALS) (64.3% vs 22.2%, 0.0%, and 2.9%, P  = .001). ALS is a high risk in male patients who have a low BMI, have leukemia as a basic disease, and have basic lung diseases (eg, BO/BOOP). CT types are mainly complex ALS, HPT, and pure PT. In addition, clinical symptoms for patients in the HPT group are severe, and there is a high prevalence of catheter drainage.